De fil palatial en aiguille patrimoniale. La soierie du cabinet de repos du petit appartement de Napoléon Ier à Versailles. - Laureen Gressé-Denois (Les Cahiers de l'École du Louvre)
In spring 2024, the Château de Versailles will present the silks Napoleon I had made in Lyon for the palaces of Versailles and Trianon. From gold to bees, from flowers to shades, the textiles were never put up, as the fall of the Empire meant that they were handed over to the Garde-Meuble. Yet their destiny bears witness to the interweaving, over time, of numerous replacements, actors and discourses. From monarchical to republican regimes, from the sovereigns and silk manufacturers of yesteryear to the curators and restorers of today, they reveal a social, economic, political and cultural history in which they played an active part. To illustrate this rich future, this article looks at five aspects of agency through the biography of the colourfully embroidered gros de Tours white brocaded silk from the resting room in the emperor’s private apartments. From its creation as part of Napoleon’s recovery plan, and its replacement after 1815 for reasons of economy, to its ornamentation, which conveys a symbolic message, the history of the silks was initially shaped by economic and political intentions. As evidence of the imperial will, it was then given a memorial aura at the Château de Malmaison, dedicated to Napoleonic remembrance in the early twentieth century, before also serving as an immersive agent in the museography of the Chimay and du Midi attics at the Château de Versailles, redesigned by Gérald van der Kemp. Lastly, its impact on our heritage is illustrated by the way it has been reworked, notably at the Hôtel de Beauharnais, preserving a historical skill. Finally, the article analyses the scholarly approach and exhibition design of the 2024 Versailles exhibition.